Pregame urine specific gravity and fluid intake by national basketball association players during competition - Osterberg, K. L.; Horswill, C. A.; Baker, L. B. (Journal of Athletic Training, 2009)
Context: Urine specific gravity (USG) has been used to estimate hydration status in athletes on the field, with increasing levels of hypohydration indicated by higher USG measurements (eg, greater than 1.020). Whether initial hydration status based on a urine measure is related to subsequent drinking response during exercise or athletic competition is unclear. Objective: To determine the relationship between pregame USG and the volume of fluid consumed by players in a professional basketball game. Design: Cross-sectional study. Setting: Basketball players were monitored during Summer League competition. Patients or Other Participants: Players (n 5 29) from 5 teams of the National Basketball Association agreed to participate. Main Outcome Measure(s): Pregame USG was measured for each player on 2 occasions. Athletes were given ad libitum access to fluid during each game and were unaware of the purpose of the study. Volume of fluid intake was measured for each player. To assess sweat loss, athletes were weighed in shorts before and after each game. Results: Sweat loss ranged from 1.0 to 4.6 L, with a mean sweat loss of 2.2 +- 0.8 L. Fluid intake ranged from 0.1 to 2.9 L, with a mean fluid intake of 1.0 +- 0.6 L. Pregame USG was greater than 1.020 in 52% of the urine samples collected and was not correlated with fluid volume consumed during either of the games (r 5 0.15, P 5 .48, and r 5 0.15, P 5 .52, respectively). Conclusions: Approximately half of the players began the games in a hypohydrated state, as indicated by USG. Fluid intake during the game did not compensate for poor hydration status before competition. Furthermore, sweat losses in these players during games were substantial (greater than 2 L in approximately 20 minutes of playing time). Therefore, both pregame and duringgame hydration strategies, such as beverage availability and player education, should be emphasized.